2015
DOI: 10.1002/lsm.22424
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of porcine ligamentum flavum with Ho:YAG, q‐switched Ho:YAG, and quadrupled Nd:YAG lasers

Abstract: Background and ObjectivesLigamentum flavum (LF) is a tough, rubbery connective tissue providing a portion of the ligamentous stability to the spinal column, and in its hypertrophied state forms a significant compressive pathology in degenerative spinal stenosis. The interaction of lasers and this biological tissue have not been thoroughly studied. Technological advances improving endoscopic surgical access to the spinal canal makes selective removal of LF using small, flexible tools such as laser‐coupled fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Our study confirmed that a SELD-assisted, 1,414-nm Nd:YAG laser can effectively treat lumbar discal cyst 7,12,14) . However, this study had some limitations.…”
Section: Macnabs: Outcome Assesment Of Patients Satisfactionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our study confirmed that a SELD-assisted, 1,414-nm Nd:YAG laser can effectively treat lumbar discal cyst 7,12,14) . However, this study had some limitations.…”
Section: Macnabs: Outcome Assesment Of Patients Satisfactionsupporting
confidence: 78%
“…Therefore, SELD Currently, trans-sacral, epiduroscopicassisted, 1,414-nm Nd:YAG laser decompression (SELD) is commonly used for spinal pathologies and has been used as a minimally invasive procedure because it is associated with better visualization, precise pathology targeting, minimal collateral tissue disruption, and less bleeding. These advantages make the surgery easier to perform, improve healing, and minimize the risk of patient discomfort 7,14,18) . To the best of our knowledge, however, no studies have assessed the efficacy of the SELD-assisted, 1,414-nm Nd:YAG laser for the treatment of lumbar discal cyst.…”
Section: Introductionmentioning
confidence: 99%
“…This study, however, is unique in that it measures a large volumetric resection of tissue. Ablation properties are more commonly characterized through mass loss experiments or measurements of cross sectional width and depth of ablation craters recorded from thin slices of stained and fixed tissue . This requires, of course, that the sample be destroyed to obtain measurements.…”
Section: Discussionmentioning
confidence: 99%
“…However, within the setting of laser‐human tissue interactions (specifically the brain), much remains to be characterized. Characterization of the laser‐tissue interaction between these various pathologic and non‐pathologic tissue types (as performed in previous publications) will be essential to provide the ablation and coagulation inputs necessary to estimate the amount of tissue removed or cauterized with each cut and plan a cutting path. Once various tissues and tumor types are characterized, real‐time sensor feedback can then be used to create a controller that is capable of predicting ablation efficiency prior to each cut, as has been shown in simulation .…”
Section: Discussionmentioning
confidence: 99%
“…Plenty of works are devoted to the study of parameters of laser radiation on the material [1][2][3][4]. However there are no separate studies on the effect of the pulse repetition rate on the ablation process and, in some cases, this parameter is a result of preselected durations and energies of the laser pulse.…”
Section: Introductionmentioning
confidence: 99%